2010
DOI: 10.1007/s11483-009-9144-5
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Rheological Characterization of Gum Tragacanth Exudates from Six Species of Iranian Astragalus

Abstract: The flow behavior of six species of Iranian gum tragacanth dispersions was investigated at different temperatures and ionic strengths, within a concentration range (0.05-1.5% w/w) using a controlled shear rate rheometer. The steady shear measurements showed that all of the gum dispersions had shear-thinning natures. The power law model was used to describe the rheological properties of dispersions and Arrhenius model was used to evaluate the temperature effect. Composition analysis, surface tension measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 148 publications
(96 citation statements)
references
References 28 publications
(40 reference statements)
8
88
0
Order By: Relevance
“…Pourable, creamy mouth feel and good flavour-release properties of GT were also previously stated by Balaghi, Mohammadifar, Zargaraan, Gavlighi, and Mohammadi (2011) and Levy and Schwarz (1958). The compositions and rheological properties of hydrocolloids are determinants for their usage (Balaghi, Mohammadifar, & Zargaraan, 2010).…”
Section: Introductionsupporting
confidence: 54%
“…Pourable, creamy mouth feel and good flavour-release properties of GT were also previously stated by Balaghi, Mohammadifar, Zargaraan, Gavlighi, and Mohammadi (2011) and Levy and Schwarz (1958). The compositions and rheological properties of hydrocolloids are determinants for their usage (Balaghi, Mohammadifar, & Zargaraan, 2010).…”
Section: Introductionsupporting
confidence: 54%
“…Moisture percentage showed no significant difference (P >0.05) between control and treatment products, although there was slight increase in moisture content of ERMC with increasing levels of GT, which might be due to a water insoluble fraction of GT called bassorin. Balaghi et al (2010) had reported that bassorin had the capacity to swell and form a gel. There was no significant difference (P >0.05) in protein percentage between control and treatment products.…”
Section: Physico-chemical Analysismentioning
confidence: 99%
“…Because of its high acid stability, the gum is well suited for use in the low pH products (Verbeken et al 2003). It consists of two main fractions: a water-insoluble component called bassorin, which has the capacity to swell and form a gel, and a water-soluble component called tragacanthin (Balaghi et al 2010). Although the physicochemical properties and steady-state rheological evaluation of gum tragacanth have been recently established, only a few studies have dealt with the viscoelastic behavior of gum tragacanth (Mohammadifar et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…9 Gum tragacanth is made up of highly substituted, heterogeneous hydrophilic polysaccharides containing Larabinose, D-galactose, D-glucose, D-xylose, L-fucose, L-rhamnose, and D-galacturonic acid and confers high viscosity when in aqueous solution. 10 When solubilized in water, the gum is usually categorized in a "soluble" fraction, tragacanthin, and an "insoluble" fraction, bassorin, respectively. 11 The water-soluble tragacanthin fraction appears to resemble pectin and contains linear chains of galacturonic acid (probably 1,4-α-linked) and arabinogalactan structures 12 as well as fuco-xylogalacturonans, whereas bassorin is believed to be mainly composed of a mixture of xylo-and fuco-xylo-substituted polysaccharides.…”
Section: ■ Introductionmentioning
confidence: 99%